The Effect of self-Compassion Training on the Quality of life Components of Mothers of Children with Attention deficit / hyperactivity Disorder - Alireza Mohammadi Sangachin Doost; Abbasali Hossein Khanzadeh; Maryam Kousha; Ashkan Naseh (Ravānshināsī-i Afrād-i Istis̠nāyī, 2022)
The aim of this study was to evaluate the effectiveness of self-compassion training on the quality of life of mothers of children with attention-deficit / hyperactivity disorder. In this study, a quasi-experimental method with a pre-test-post-test design with a control group was used and its statistical population also included mothers of children aged 5 to 11 years, boys and girls with attention-deficit/hyperactivity disorder in Rasht in 2020-2021. The study sample consisted of 28 mothers from the statistical population selected by convenience sampling method and randomly placed in experimental and control groups. The experimental group participated in the compassion training group as a group for 8 weekly sessions. Both groups were evaluated in two stages of pre-test and post-test with the Short Form Quality of Life Questionnaire (1996). The results showed that the self-compassion training intervention had a significant effect on the scores of quality of life components (physical health, psychological health, social relations, and environmental health), in the post-test stage the scores of quality of life of the experimental group increased significantly (p <0.001). Self-compassion training in comparison with other kinds of training can have very useful results for mothers, especially in order to increase their quality of life, and can be introduced and implemented as one of the axes of parental training in comparison with other methods and training.